Ensuring the Stability of our National Currency in the Formation of the Term Foreign Exchange Market - o’g’li, Akbarov Husniddinjon Mo’ysin (European Journal of Life Safety and Stability (2660-9630), 2021)
The Central Bank is currently taking large-scale measures independently to form a fixed-term currency market and ensure the stability of the national currency. In this article, we have outlined our views and suggestions on how to regulate the foreign exchange market in our economy and ensure the stability of our national currency.